Phloem exudate metabolic content reflects the response to water‐deficit stress in pea plants (Pisum sativum L.). (6th May 2021) - Blicharz, Sara; Beemster, Gerrit T.S.; Ragni, Laura; De Diego, Nuria; Spíchal, Lukas; Hernándiz, Alba E.; Marczak, Łukasz; Olszak, Marcin; Perlikowski, Dawid; Kosmala, Arkadiusz; Malinowski, Robert
Summary: Drought stress impacts the quality and yield of Pisum sativum . Here, we show how short periods of limited water availability during the vegetative stage of pea alters phloem sap content and how these changes are connected to strategies used by plants to cope with water deficit. We have investigated the metabolic content of phloem sap exudates and explored how this reflects P. sativum physiological and developmental responses to drought. Our data show that drought is accompanied by phloem‐mediated redirection of the components that are necessary for cellular respiration and the proper maintenance of carbon/nitrogen balance during stress. The metabolic content of phloem sap reveals a shift from anabolic to catabolic processes as well as the developmental plasticity of P. sativum plants subjected to drought. Our study underlines the importance of phloem‐mediated transport for plant adaptation to unfavourable environmental conditions. We also show that phloem exudate analysis can be used as a useful proxy to study stress responses in plants. We propose that the decrease in oleic acid content within phloem sap could be considered as a potential marker of early signalling events mediating drought response. Significance Statement: We describe the changes in phloem metabolic content of pea ( Pisum sativum ) plants subjected to drought and show how the observed patterns reflect physiological and developmental responses. Phloem exudate analysis itself gives us a clear and informative picture of the stress response strategy centred on above‐ground growth reduction and the reuse and redistribution of carbon and nitrogen. This provides evidence for the importance of phloem‐mediated long‐distance coordination in plant responses to drought. Fluctuations of particular metabolites in vascular sap can be used to monitor drought response in pea plants.